The role of climate change in regulating Arctic permafrost peatland hydrological and vegetation change over the last millennium - Zhang, Hui; Piilo, Sanna Riikka; Amesbury, Matthew J.; Charman, Dan J.; Gallego-Sala, Angela V.; Väliranta, Minna Maria (Quaternary Science Reviews, 2019)
Climate warming has inevitable impacts on the vegetation and hydrological dynamics of high-latitude permafrost peatlands. These impacts in turn determine the role of these peatlands in the global biogeochemical cycle. Here, we used six active layer peat cores from four permafrost peatlands in Northeast European Russia and Finnish Lapland to investigate permafrost peatland dynamics over the last millennium. Testate amoeba and plant macrofossils were used as proxies for hydrological and vegetation changes. Our results show that during the Medieval Climate Anomaly (MCA), Russian sites experienced short-term permafrost thawing and this induced alternating dry-wet habitat changes eventually followed by desiccation. During the Little Ice Age (LIA) both sites generally supported dry hummock habitats, at least partly driven by permafrost aggradation. However, proxy data suggest that occasionally, MCA habitat conditions were drier than during the LIA, implying that evapotranspiration may create important additionaleco-hydrological feedback mechanisms under warm conditions. All sites showed a tendency towards dry conditions as inferred from both proxies starting either from ca. 100 years ago or in the past few decades after slight permafrost thawing, suggesting that recent warming has stimulated surface desiccation rather than deeper permafrost thawing. This study shows links between two important controls over hydrology and vegetation changes in high-latitude peatlands: direct temperature-induced surface layer response and deeper permafrost layer-related dynamics. These data provide important backgrounds for predictions of Arctic permafrost peatlands and related feedback mechanisms. Our results highlight the importance of increased evapotranspiration and thus provide an additional perspective to understanding of peatland-climate feedback mechanisms. (C) 2018 Elsevier Ltd. All rights reserved. Peer reviewed